Study on blood condition of Pangasius hypophthalmusin the Tapung Kiri River and the Sail River, Riau Province - Satria Flamboyan Siregar; Eddiwan Eddiwan; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Pangasius hypophthalmus is a type of freshwater fish that inhabit the Sail River that is polluted and the Tapung Kiri River that has relatively good water quality. As the water quality in general affects the blood condition of the fish, it is predicted that blood condition of P. hypophthalmus from the Tapung Kiri River and the Sail River different. A research aims to understand blood condition of P.hypophthalmus from both areas has been conducted from February to March 2019. There are 12 fishes from the Tapung Kiri River and 12 fishes from the Sail River. The fish blood was taken and analyzed for erythrocytes and leukocytes content, hematocrite and leucocrite levels and types of leukocytes present. Results shown that the erythrocytes, leukocytes, hematocrite and leucocrite of fish from the Tapung Kiri River was 2.620.833 cells/mm3, 242.958 cells/mm3, 35,6% and 1,54% respectively. While those of the Sail River was 1.887.500 cells/mm3, 310.500 cells/mm3, 28,75% and 2,62%. In the fish from both areas, there were 5 types of white blood cells.  In the fish  from the Tapung Kiri River, there were lymphocytes 85,6%, monocytes 2,9%, thrombocytes 9,7%, eosinophils 0,8% and neutrophils 0,8% respectively. While those of the Sail River were lymphocytes 56,3%, monocytes 5%, thrombocytes 37,1%, eosinophils 0,8% and neutrophils 0,8%. Based on data obtained, it can be concluded that the fish from the Tapung Kiri River is healthy while the fish from the Sail River is not healthy. Keywords: blood, erythrocytes, leukocytes, hematocrite and leucocrite